Variation and change in instrument noun formation in Hebrew and its relation to the verbal system. (April 2015) - Laks, Lior
Abstract : This paper examines morphological variation and change in the formation of instrument nouns in Hebrew. The change is always from one of the non-participle templates into a participle template and never the other way around. Nonetheless, not all instrument nouns (INs) change their template. I contend that the transition to the participle templates can be predicted based on systematic criteria. Such a change targets both morphological and thematic transparency between the IN and the related verb. Thematically, the participle IN corresponds to a thematic role that the verb assigns. The IN has to be agentive in order to be thematically transparent and undergo morphological change. The more transparent the thematic relation between the verb and the IN is, the greater the chance for morphological change. Morphologically, the formation of the participle form is also more transparent as it requires fewer changes between the verb and the IN. The only changes that occur are affixation and changing the vowels of the base verb, and the formation in the participle templates preserves the prosodic structure of the base verb. The analysis also provides further support to the stem modification theory and shows that the formation of the instrument noun is based on internal changes on the verbal base form without separate reference to the consonantal root.